Diffusion of innovations. - Rogers, Everett M. (Everett Mitchel), 1931-2004 (New York : The Free Press, 2003)
Ch. 1 Elements of Diffusion Ch. 2 A History of Diffusion Research Ch. 3 Contributions and Criticisms of Diffusion Research Ch. 4 The Generation of Innovations Ch. 5 The Innovation-Decision Process Ch. 6 Attributes of Innovations and Their Rate of Adoption Ch. 7 Innovativeness and Adopter Categories Ch. 8 Diffusion Networks Ch. 9 The Change Agent Ch. 10 Innovation in Organizations Ch. 11 Consequences of Innovations Glossary Bibliography Name Index Subject Index
Keywords: Innovatie